Losartan, a selective antagonist of AT1 receptor, attenuates seawater inhalation induced lung injury via modulating JAK2/STATs and apoptosis in rat. (August 2017) - Li, Congcong; Bo, Liyan; Li, Pengcheng; Lu, Xi; Li, Wangping; Pan, Lei; Sun, Yani; Mu, Deguang; Liu, Wei; Jin, Faguang
Abstract: Losartan is a selective antagonist of AngⅠ type (AT1) receptor of Angiotensin Ⅱ (Ang Ⅱ), which is widely used as a clinical medicine for the hypertension. Recent studies have shown that losartan was shown to protect from acute lung injury (ALI). However, the underlying mechanism remains unclear. The aim of this research was to clarify whether Ang Ⅱ participated in the inflammatory response of ALI induced by seawater inhalation, and whether losartan had the protective effects on ALI by blocking the combination of Ang Ⅱ and AT1 receptor. In the current study, the severity of lung injury and the inflammatory reactions during seawater drowning induced ALI were assessed. Besides, we also detected the activation of relative pathways such as NF-κB, JAK2/STATs and apoptosis. The results showed that seawater inhalation could up-regulate the expression of Ang Ⅱ and AT1. While pretreatment of losartan (especially 15 mg/kg and 30 mg/kg) alleviated lung injury by inhibiting Ang-Ⅱ and AT1 receptor combination and in turn decreased the expression of p-NF-κB and activation of JAK2/STATs pathway. We also confirmed that losartan could reduce the apoptotic ratio of cells in the lung by modulating the phosphorylation of JNK and leak of cytochrome C to cytosol. Taken together, these findings demonstrate that losartan might have a therapeutic potential as an anti-inflammatory agent for treating SWI-ALI.